2016
DOI: 10.21649/akemu.v12i1.812
|View full text |Cite
|
Sign up to set email alerts
|

Association of ABO and Rh blood group systems with blood pressure in a population sample from Peshawar, NWFP, Pakistan

Abstract: Background: Abundant literature is available on the association of blood groups to various diseases. It was thus hypothesized that similar linkage may also exist between blood groups and Hypertension, which prompted me to work on this project. Material and Methods: This study was carried out from June 2001 to September 2003 on 1304 subjects out of which 756 were male and 548 were females. Age ranged from 18-65 years. The blood groups and blood pressure were determined in PMRC Research Center KMC Peshawar, by u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 1 publication
0
0
0
Order By: Relevance
“…Another Indian study conducted by Richa et al at Agra showed agreement with our ndings. However, numbers of studies disagree with our ndings including; Salam et al conducted a study on young adults of Khyber Medical College of Peshawar found A blood group is more prone to develop hypertension [11]. Another Pakistani study conducted by Altaf B et al on medical college students of Faisalabad concluded that subjects with blood group A were more likely to develop hypertension followed by O blood group subjects [12].…”
Section: Discussioncontrasting
confidence: 66%
“…Another Indian study conducted by Richa et al at Agra showed agreement with our ndings. However, numbers of studies disagree with our ndings including; Salam et al conducted a study on young adults of Khyber Medical College of Peshawar found A blood group is more prone to develop hypertension [11]. Another Pakistani study conducted by Altaf B et al on medical college students of Faisalabad concluded that subjects with blood group A were more likely to develop hypertension followed by O blood group subjects [12].…”
Section: Discussioncontrasting
confidence: 66%